2015
DOI: 10.17554/j.issn.2313-5611.2015.01.15
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Possible Role of NOS-NO-ADMA Pathway Dysfunction in the Development of Cognitive Decline and Dementia: Exploring the Vascular Features of Alzheimer’s Disease

Abstract: In recent years significant overlap between cardio-metabolic risk factors and cognitive decline has been reported. Cardio-metabolic and vascular factors shown to be associated with Alzheimer's disease (AD) and other forms of dementia include midlife diabetes and hypertension, cerebrovascular lesions, diminished vascular function, dyslipidemia, obesity, and cigarette smoking. Accordingly, it has been recently proposed that amyloid is not the cause of AD but merely a marker and a later consequence of upstream ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Noteworthy, contradicting results concerning ADMA have even been reported by the same group 11,24 stressing ADMA level dependence on cohort characteristics. The ADMA accumulation is expected in the conditions of oxidative stress and inflammation as a result of the up-regulated expression of PRMT enzymes (increased rate of ADMA synthesis) and the down-regulated expression of DDAH enzymes (decreased rate of ADMA degradation) 7 . However, Morales et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noteworthy, contradicting results concerning ADMA have even been reported by the same group 11,24 stressing ADMA level dependence on cohort characteristics. The ADMA accumulation is expected in the conditions of oxidative stress and inflammation as a result of the up-regulated expression of PRMT enzymes (increased rate of ADMA synthesis) and the down-regulated expression of DDAH enzymes (decreased rate of ADMA degradation) 7 . However, Morales et al .…”
Section: Discussionmentioning
confidence: 99%
“…Brain homeostasis is secured by the activity of endothelial and neuronal isoforms of nitric oxide synthase (respectively eNOS and nNOS), catalyzing a two-step oxidation of L-arginine to NO and L-citrulline 7 . The NOS enzymes are negatively regulated by methylated derivatives of L-arginine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have detected changes in the expression and activity of NO metabolites, donors, and NOS/NO itself in the brains of AD and VaD patients [ 82 , 83 , 84 ]. A review on animal stroke models showed that a supplemented NO donor improves overall CBF and reduces infarct size [ 85 ].…”
Section: Nos/no Pathway Plays a Key Role In Various Pathogenesis Of Vadmentioning
confidence: 99%
“…These results suggest that these three NOS subtypes play completely different roles in their respective regions and collectively affect the functions of brain. Currently, it has been proven that alterations of the NOS/NO pathway in VaD pathology manifest as a decrease of eNOS activity and the excessive activation of nNOS and iNOS [ 79 , 82 ].…”
Section: Nos/no Pathway Plays a Key Role In Various Pathogenesis Of Vadmentioning
confidence: 99%